Comparison of image quality between simultaneous multi-slice single-shot EPI and readout-segmented EPI in diffusion-weighted imaging of prostate cancer: a retrospective study - Zhang, Tianqi; Chen, Jie; Li, Meng; Shen, Aibin (Frontiers in Oncology, 2026)
BackgroundSimultaneous multi-slice (SMS) has received a lot of attention, but there is a lack of comparative studies on the image quality and diagnostic efficacy of simultaneous multi-slice single-shot echo planar imaging (SMS+SS-EPI) versus readout-segmented echo planar imaging (RS-EPI) in diffusion-weighted imaging (DWI) of prostate cancer.ObjectivesComparison of image quality and diagnostic efficacy of SMS+SS-EPI and RS-EPI in DWI of prostate cancer.MethodsA retrospective study included 100 patients who underwent magnetic resonance imaging (MRI) between January and August 2025 (48 cases with SMS+SS-EPI and 52 cases with RS-EPI). Two radiologists performed blinded 5-point subjective scoring and measured lesion signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), contrast (C), and apparent diffusion coefficient (ADC) values. Using transperineal 12+X needle biopsy pathology as the gold standard, receiver operating characteristic (ROC) curves were plotted and ADC diagnostic performance was compared.ResultsThe RS-EPI group demonstrated superior performance in clarity (4.37 ± 0.69 vs. 3.98 ± 0.79), anatomical distortion (4.06 ± 0.80 vs. 3.69 ± 0.78), sharpness (4.04 ± 0.82 vs. 3.58 ± 0.74), detail display (4.21 ± 0.72 vs. 3.75 ± 0.70), and overall quality (4.33 ± 0.68 vs. 3.88 ± 0.70) were better than those of the SMS+SS-EPI group (P<0.001). The SNR (57.65 ± 7.84 vs. 50.45 ± 6.56, P < 0.001) and CNR (4.58 ± 0.75 vs. 4.16 ± 0.73, P = 0.005) were significantly higher than those in the RS-EPI group, while C (6.43 ± 1.06 vs. 6.32 ± 1.02, P = 0.578) and ADC (0.90 ± 0.23 vs. 0.87 ± 0.21, P = 0.448) values showed no statistically significant differences. Additionally, the area under curve (AUC) values for diagnosing prostate cancer based on ADC in the two groups were 0.925 and 0.933, respectively, indicating statistical equivalence in diagnostic performance (z=0.462, P = 0.644). However, the SMS+SS-EPI group demonstrated a significantly shorter acquisition time (1 min 50 s vs. 3 min 43 s).ConclusionRS-EPI delivers superior subjective image quality, facilitating detailed anatomical assessment. SMS+SS-EPI provides higher SNR and CNR, significantly reducing scan time while maintaining comparable diagnostic performance based on ADC values. Sequence selection should be guided by clinical requirements.